ANALYSIS IMPACT CONDENSATE POLLUTION ON SOIL CONDITION OF POLTAVA - Санжаревська О. I. (Scientific Progress & Innovations, 2014)
Poltava Region is one of the leading oil and gas extraction regions of Ukraine. Almost 40 % of Ukrainian gas and every fifth ton of oil with condensate are extracted from depths of Poltava Region, which have unique fields of fuel and power as well as mineral resources. However, during extraction, transportation and processing of oil and gas condensate, oil spills occur, which is associated with accidents and unauthorized ties-in. The result is polluted soil, ground and surface water. We have identified the major negative results of influence on the soil ecosystem gas condensate. It was experimentally determined that the basic physical and chemical properties of soil contaminated with a mixture of gas condensate and comparison with uncontaminated soil mineral oil in Poltava. Conclusions were made concerning the suitability of the soil for agricultural use and possible ways to improve it. There were appeared some problems that should be solved for improving soil Poltava.